The Impact of Climate Change on Domestic and International Tourism: A Simulation Study - Andrea Bigano; Jacqueline M. Hamilton; Richard S.J. Tol (Fondazione Eni Enrico Mattei (FEEM), 2006)
We use an updated and extended version of the Hamburg Tourism Model to simulate the effect of development and climate change on tourism. Model extensions are the explicit modelling of domestic tourism and the inclusion of tourist expenditures. We also use the model to examine the impact of sea level rise on tourism demand. Climate change would shift patterns of tourism towards higher altitudes and latitudes. Domestic tourism may double in colder countries and fall by 20% in warmer countries (relative to the baseline without climate change). For some countries international tourism may treble whereas for others it may cut in half. International tourism is more (less) important than is domestic tourism in colder (warmer) places. Therefore, climate change may double tourist expenditures in colder countries, and halve them in warmer countries. In most places, the impact of climate change is small compared to the impact of population and economic growth. The quantitative results are sensitive to parameter choices, but the qualitative pattern is robust.
Keywords: L83; Q54; 330; Climate Change; International Tourism; Domestic Tourism; Tourismus; Internationaler Tourismus; Klimaveränderung; Simulation; Welt